The influence of entrepreneurship education towards entrepreneurial intention mediated by attitude, subjective norms, and perceived behavioral control of business management students at Universitas Ciputra Surabaya - Cynthia Hartono; Wendra Hartono; Charly Hongdiyanto; Gracia Ongkowijoyo (President University, 2022)
One of the major problems in Indonesia is inadequate number of workers with the number of job positions available. Hence, it is better for people with productive age, especially the one that is educated, to have an orientation or intention to create job, rather than being a job seeker. Entrepreneurship education is considerably believed to be a prominent element in forming one’s entrepreneurial intention. Nevertheless, many studies show few consistent results on the direct impact of entrepreneurship education on individual's entrepreneurial intention. Therefore, the aim of this study is to examine the influence of entrepreneurship education toward entrepreneurial intention with Theory of Planned Behaviour (TPB) approach as a mediator. This theory clarified that there are three primary forces that influence an individual's intentions, which are attitude, subjective norms, and perceived behavioural control. The approach to this research is quantitative method, where the data collected will be analysed statistically using PLS-SEM. The researcher selected the population of 992 business management students at Universitas Ciputra Surabaya, who are registered in the academic year of 2017 and 2018. By using purposive sampling method, the total samples that successfully collected are 305 samples. The result of this study concludes that the direct relationship between entrepreneurship education to entrepreneurial intention shows no significant effect. Nevertheless, entrepreneurship education can significantly influence entrepreneurial intention if it is fully mediated by attitude toward entrepreneurship, subjective norms, and perceived behavioural control. Ajzen, I.(1988).Attitudes,Personality,andBehavior. Chicago:DorseyPress. Ajzen, I. (1991). The Theory of Planned Behavior. Organizational Behavior and HumanDecisionProcesses,Vol. 50, No. 2, 179-211. Basu, A., & Virick, M. (2008). Assessing Entrepreneurial Intentions Amongst Students: AComparative Study. 12th Annual Meeting of the National Collegiate Inventors andInnovatorsAlliance, Dallas, USA, 19-21. Bui, T. H. V., Nguyen, T. L. T., Tran, M. D., & Nguyen, T. A. T.T. (2020). DeterminantsInfluencingEntrepreneurialIntentionamongUndergraduatesinUniversitiesofVietnam,Journalof Asian Finance, Economics andBusiness,7(7): 369-378 Do Paco, A. et al. (2011). Behaviours and Entrepreneurial Intention: Empirical Findings About Secondary Students. Journal of International Entrepreneurship, Vol. 9 No. 1, 20-38. Farooq, M. et al. (2018). Impact of support from social network on entrepreneurial intention of fresh business graduates A structural equation modelling approach. Education + Training, Vol. 60, No. 4, 335-353. Galloway, L., & Brown, W. (2002). Entrepreneurship Education at University: A Driver in the Creation of High Growth Firms? Education+Training, Vol. 44 No. 8/9, 398-405. Garson, G. (2016). Partial Least Squares: Regression & Structural Equation Models. Statistical Associates Publishing. Gerba, D. (2012). Impact of entrepreneurship education on entrepreneurial intentions of business and engineering students in Ethiopia. African Journal of Economic and Management Studies.Vol. 3, No. 2., 258 - 277. Hair, Jr., J. et al. (2017). A Primer on Partial Least Squares Structural Equation Modeling (PLS-SEM) Second Edition. Los Angeles: Sage Publication. Kshetri, N. (2018). Global Entrepreneurship. Global Entrepreneurship. https://doi.org/10.4324/9780429458996 Kuehn, K. (2008). Entrepreneurial intentions research: implications for entrepreneurship education. Journal of Entrepreneurship Education, Vol. 11, 87-98. Kusmintarti, A., Riwajanti, N. I., & Asdani, A. (2017). Pendidikan Kewirausahaan dan Intensi Kewirausahaan dengan Sikap Kewirausahaan sebagai Mediasi. Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, Vol. 2 No. 2, 119-128.Luc, P. T. (2020). Outcome Expectations and Social Entrepreneurial Intention: Integration of Planned Behavior and Social Cognitive Career Theory. The Journal of Asian Finance, Economics and Business, 7(6): 399-407. Lu, H., & Wang, J. (2018). Entrepreneurial Intention of Two Patterns of Planned Behaviour and Alertness: Empirical Evidence in China. The Journal of Asian Finance, Economics and Business, 5(2): 63-72. Paray, Z., & Kumar, S. (2020). Does entrepreneurship education inﬂuence entrepreneurial intention among students in HEI’s? The role of age,gender and degree background. Journal of International Education in Business, Vol. 13 No. 1, 55-72. Phan, L. T. (2018). The Relationship between Perceived Access to Finance and Social Entrepreneurship Intentions among University Students in Vietnam. Journal of Asian Finance Economics and Business, 5(1), 63-72. Pratana, N. K., & Margunani. (2019). Pengaruh Sikap Berwirausaha, Norma Subjektif dan Pendidikan Kewirausahaan Terhadap Intensi Berwirausaha. Economic Education Analysis Journal, Vol. 8 No. 2, 533-550. Puni, A., Anlesinya, A., & Korsorku, P. (2018). Entrepreneurial education, self-efficacy and intentions in Sub-Saharan Africa. African Journal of Economic and Management Studies, Vol. 9 No. 4, 492-511. Rasli, A. et al. (2013). Factors Affecting Entrepreneurial Intention Among Graduate Students of Universiti Teknologi Malaysia. International Journal of Business and Social Science.Vol. 4 No. 2, 182-188 . Santi, N., Hamzah, A., & Rahmawati, T. (2017). Pengaruh Efikasi Diri, Norma Subjektif, Sikap Berperilaku, dan Pendidikan Kewirausahaan Terhadap Intensi Berwirausaha. Jurnal Inspirasi Bisnis dan Manajemen, Vol. 1 No. 1, 63-74. Schwarz, E. et al. (2009). The effects of attitudes and perceived environment conditions on students’ entrepreneurial intent: an Austrian perspective. Education Training, Vol. 51 No. 4, 272-291. Sekaran, U., & Bougie, R. (2016). Research Method for Business: A Skill-Building Approach Seventh Edition. Chichester UK: John Wiley & Sons Ltd. Souitaris, V., Zerbinati, S., & Al-Laham, A. (2007). Do entrepreneurship programmes raise entrepreneurial intention of science and engineering students? The effect of learning, inspiration and resources. Journal of Business Venturing, Vol. 22 No. 4, 566-591. Sun, H. et al. (2017). The impact of entrepreneurial education on entrepreneurial intention of engineering students in HongKong. Management Decision, Vol. 55 No. 7, 1371-1393. Thompson, E. (2009). Individual entrepreneurial intent: construct clarification and development of an internationally reliable metric. Entrepreneurship Theory and Practice, Vol. 33 No. 3, 669-694. Utami, C. W. (2017). Attitude, Subjective Norms, Perceived Behavior, Entrepreneurship Education and Self-efficacy toward Entrepreneurial Intention University Student in Indonesia . European Research Studies Journal Volume XX, Issue 2A, 475-495 . Wilson, F., Kickul, J., & Marlino, D. (2007). Gender, entrepreneurial self-efficacy, and entrepreneurial career intentions: implications for entrepreneurship education. Entrepreneurship Theory and Practice, Vol. 31 No. 3, 387-406. Zhang, F. et al. (2019). How entrepreneurial learning impacts one’s intention towards entrepreneurship: A planned behavior approach. Chinese Management Studies, Vol. 13 No. 1, 146-170.